Developmental changes in dendritic shape and synapse location tune single-neuron computations to changing behavioral functions - Meseke, Maurice; Evers, Jan-Felix; Duch, Carsten (Journal of neurophysiology, 2009)
During nervous system development, different classes of neurons obtain different dendritic architectures, each of which receives a large number of input synapses. However, it is not clear whether synaptic inputs are targeted to specific regions within a dendritic tree and whether dendritic tree geometry and subdendritic synapse distributions might be optimized to support proper neuronal input-output computations. This study uses an insect model where structure and function of an individually identifiable neuron, motoneuron 5 (MN5), are changed while it develops from a slow larval crawling into a fast adult flight motoneuron during metamorphosis. This allows for relating postembryonic dendritic remodeling of an individual motoneuron to developmental changes in behavioral function. Dendritic architecture of MN5 is analyzed by three-dimensional geometric reconstructions and quantitative co-localization analysis to address the distribution of synaptic terminals. Postembryonic development of MN5 comprises distinct changes in dendritic shape and in the subdendritic distribution of GABAergic input synapses onto MN5. Subdendritic synapse targeting is not a consequence of neuropil structure but must rely on specific subdendritic recognition mechanisms. Passive multicompartment simulations indicate that postembryonic changes in dendritic architecture and in subdendritic input synapse distributions may tune the passive computational properties of MN5 toward stage-specific behavioral requirements.